(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses an algorithm for dividing natural language texts into word forms and an algorithm for analyzing and synthesizing word form affixes in the resulting dictio- nary. Each created algorithm was developed taking into account the rules of natural language.